(untitled) (Iranian Journal of Kidney Diseases, 2014)
Myelosuppression is the life-threatening adverse effect of methotrexate. Impaired kidney function is a major aggravating factor of methotrexate-induced myelosuppression. In end-stage renal disease patients, methotrexate therapy must be with cautious because the efficacy of removal of methotrexate by means of dialysis is in doubt. In clinical practice, low-dose methotrexate is still used by clinicians in treatment of dialysis patients with immunological disorders. We reported a 61-year-old woman on continued ambulatory peritoneal dialysis who developed pancytopenia with a nadir leukocyte count of 0.03 × 109/L, leading to severe sepsis after 3 doses of methotrexate, 7.5 mg weekly. We highlighted that methotrexate therapy in dialysis patients, even with low doses could impose the risk of myelosuppression, causing a fatal outcome. Alternative medications to methotrexate might be recommended in dialysis patients.